Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jms.4341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aprotic solvents on the stability of metal‐free superoxide dismutase probed by native electrospray ionization–ion mobility–mass spectrometry

Abstract: Considering that aprotic solvents are often used as cosolvents in investigating the interactions between small molecules and proteins, we assessed the effects of five aprotic solvents represented by dimethylformamide (DMF) on the structure stabilities of metal‐free SOD1 (apo‐SOD1) by native electrospray ionization–ion mobility–mass spectrometry (ESI‐IM‐MS). These aprotic solvents include DMF, 1,3‐dimethyl‐2‐imidazolidinone (DMI), dimethyl sulfoxide (DMSO), acetonitrile (ACN), and tetrahydrofuran (THF). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the study, the interaction between four flavanones and apo-SOD1 In previous studies, the dominating dimer species of apo-SOD1 were observed through ESI-MS, and the observed charge states ranged from +11 to +13. 24,28 Apo-SOD1 mainly exists in the form of dimers under the "near-native" experimental conditions. There is a little monomeric apo-SOD1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, the interaction between four flavanones and apo-SOD1 In previous studies, the dominating dimer species of apo-SOD1 were observed through ESI-MS, and the observed charge states ranged from +11 to +13. 24,28 Apo-SOD1 mainly exists in the form of dimers under the "near-native" experimental conditions. There is a little monomeric apo-SOD1.…”
Section: Resultsmentioning
confidence: 99%
“…apo-SOD1 was prepared by demetallation protocol. 24,25 Briefly, 1 mL of SOD1 stock solution was dialyzed for 24 h in a 20mM NH 4 OAC buffer (pH 3.2) containing 5mM EDTA. After 24 h, the dialysis solution was then replaced with 20mM NH 4 OAC buffer (pH 3.2) without EDTA.…”
Section: Sample Preparationmentioning
confidence: 99%
“…and apo-SOD1 can be calculated by the corresponding Equations 1 13 and 2. I di and I mon represent the exported peak intensities of the dimeric and monomeric species from the corresponding regions of the ion mobility profiles, respectively.…”
Section: The Contents Of Dimer and Compaction Conformation Of Sod1mentioning
confidence: 99%